2023
DOI: 10.3389/fmicb.2023.1253480
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic properties of Bacillus subtilis DG101 isolated from the traditional Japanese fermented food nattō

Cecilia Leñini,
Facundo Rodriguez Ayala,
Anibal Juan Goñi
et al.

Abstract: Spore-forming probiotic bacteria offer interesting properties as they have an intrinsic high stability, and when consumed, they are able to survive the adverse conditions encountered during the transit thorough the host gastrointestinal (GI) tract. A traditional healthy food, nattō, exists in Japan consisting of soy fermented by the spore-forming bacterium Bacillus subtilis natto. The consumption of nattō is linked to many beneficial health effects, including the prevention of high blood pressure, osteoporosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…Different Bifidobacteria and Lactobacilli strains have been demonstrated to extend nematode lifespan, mainly through modulations in the p-38 mitogen-activated protein kinases (p38-MAPK) signaling pathway [26]. For example, a recent study demonstrated that supplementation with Bacillus subtilis DG101, isolated from the traditional Japanese fermented food Nattō, extended worm lifespan by 45% and improved chemotaxis, in comparison with E. coli OP50-fed worms [27]. Similarly, supplementation with Lacticaseibacillus casei 62 and Lacticaseibacillus casei 63 increased nematode lifespan by improving the mitochondrial function, suggesting these bacterial strains as potential probiotics in sarcopenia [28].…”
Section: Probiotics With Lipid-reducing Activity In C Elegansmentioning
confidence: 99%
“…Different Bifidobacteria and Lactobacilli strains have been demonstrated to extend nematode lifespan, mainly through modulations in the p-38 mitogen-activated protein kinases (p38-MAPK) signaling pathway [26]. For example, a recent study demonstrated that supplementation with Bacillus subtilis DG101, isolated from the traditional Japanese fermented food Nattō, extended worm lifespan by 45% and improved chemotaxis, in comparison with E. coli OP50-fed worms [27]. Similarly, supplementation with Lacticaseibacillus casei 62 and Lacticaseibacillus casei 63 increased nematode lifespan by improving the mitochondrial function, suggesting these bacterial strains as potential probiotics in sarcopenia [28].…”
Section: Probiotics With Lipid-reducing Activity In C Elegansmentioning
confidence: 99%
“…Petri dishes were filled out by the nutrient media prepared by the same method (Section S2, Supplementary). The surface of the nutrient media was inoculated by bacteria suspension using Drygalsky spatula [56]. Finally, the impregnated disks were placed on the inoculated nutrient media and incubated at 37 • C for 24 h. After incubation, the diameter of the growth inhibition zones was measured.…”
Section: Potential Antibacterial and Fungicidal Activity Of Se Nps-ctacmentioning
confidence: 99%